THE USE OF AUDIO VISUAL MEDIA ON LEARNING SIGEH PENGUTEN DANCE AT IV B CLASS OF SD NEGERI 1 BANDAR AGUNG - NOVITA WATI; fitri daryanti; muhammad fuad; susi wedhyaningsih (Jurnal Seni dan Pembelajaran, 2013)
The objective of this research is to describe the use of audio visual median and students’ achievement on the learning of sigeh penguten dance at IV B class of SD Negeri 1 Bandar Agung.The research method which is used was descriptive qualitative through the theory that is used was the learning, media of learning and audio visual media. The source of the data in this research were the teacher of arts and culture and the students at IV B class who are following the learning of sigeh penguten dance which consist of 15 students. The data collecting techniques which are used were observation, documentary in form of field note, photo and video, interviewing the arts and culture teacher and students, research instrument in form of test and practice and monitoring students’ activities and monitoring teacher’s activities.The result of this research shows that the implementation of the learning of sigeh pengunten dance through learning media begin with teacher prepare the laptop, LCD, and sound system. Then, teacher shows the video of sigeh penguten dance which consists of three views that is, the video of basic movement technique, the video of basic movement series, and the video view of the complete dance with the music, make up, and costume. After that the teacher shows the video of movements technique first, after the students are able to remember the movement series of the teacher, teacher shows the video views of the complete dance with music, make up, and costume to make the students are able to remember the movement in accordance with the music along the dance. The views of video sigeh penguten dance have done repeatedly until the students really remember it. In learning, the students were more head for the video of sigeh peguten dance therefore the students’ dance movements only limited on the remembering the steps of movement series and were not following the true technique.Consequently, the result the students learning achievement in sigeh penguten dance at SD Negeri 1 Bandar Agung in the category of less good. Seeing from the ability of students’ dance in each aspects of movements technique belonging to less good that is on the technique of the students’ head movement, students are able to modeling the head movement with the exact technique’ appropriate with the video of sigeh penguten dance but the level of false 3-4 times, on the technique of students’ hand movement exactly appropriate with the video of sigeh penguten dance but with the level of false 5-6 times. The memorization of the movement steps included on the category good that is the students are able to modeling the series of movement dance from the first of movement series until2the end but in level of false 1-2 times. The accuracy movement with the music included in category less good that is the students are modeling movement dance 5-6 times late or before the music and were not appropriate with the tempo, rhythm and the calculation in each movement steps.